Cost-Effectiveness of Real-World Administration of Concomitant Viscum album L. Therapy for the Treatment of Stage IV Pancreatic Cancer. (13th March 2020) - Thronicke, Anja; Reinhold, Thomas; von Trott, Philipp; Matthes, Harald; Schad, Friedemann
Abstract : Background . For patients receiving add-on Viscum album L. (VA) treatments for late-stage pancreatic cancer, an improved overall survival (OS) was observed. Only limited information regarding cost-effectiveness (CE) for comparisons between standard of care and standard of care plus add-on VA in stage IV pancreatic cancer treatment is available. The present study assessed the costs and cost-effectiveness of standard of care plus VA (V) compared to standard of care alone (C) for a hospital in Germany. Methods . An observational study was conducted using data from the Network Oncology clinical registry. Patients included had stage IV pancreatic cancer at diagnosis and received C or V treatment in a certified German Cancer Center. Cost and cost-effectiveness analyses (CEA) including the analysis of the incremental cost-effectiveness ratios (ICER) were performed from the hospital's perspective based on routine data from the financial controlling department and observed data on OS. The primary result of the analysis was tested for robustness in a bootstrap-based sensitivity analysis. Results . 88 patients ( C : n  = 34; V : n  = 54) were included, with a mean age 65.6 years and proportion of male patients 48.9%. Adjusted hospital's total mean costs for patients from the C and V groups were €10068.97 (over an adjusted mean OS time of 7.1 months) and €12267.94 (over an adjusted mean OS time of 10.6 months), respectively. As to CEA analysis, a relevant total hospital's savings of €260.81/month mean OS for V patients compared to C was calculated. The costs per additional OS month gained (ICER) with the V treatment compared to C were €628.28. Furthermore, a relevant hospital savings of €915.77 per mean hospital stay and additional costs of €75.09 per mean hospitalization day in the V group were observed compared to C . Conclusion . Based on this CEA analysis, from the hospital's point of view, the costs per mean month of OS and per mean hospital stay were lower for patients under combinational standard of care plus VA compared to patients receiving standard of care alone for the treatment of stage IV pancreatic cancer. Further prospective cost-effectiveness studies are mandatory to reevaluate our findings.